"Psychologically and emotionally, it affects me 'til this day": exploration of childhood sexual abuse perspectives among older adults living with HIV in South Carolina. (28th October 2022) - Brown, Monique J.; Nkwonta, Chigozie A.; Kaur, Amandeep; James, Titilayo; Conserve, Donaldson F.; Small, Brent J.; Haley, William E.
ABSTRACT: Objectives: The influence of childhood sexual abuse (CSA) may be seen immediately or across the life course. CSA is also associated with increased HIV-risk behavior, and greater likelihood of an HIV/STI diagnosis. The aim of this study was to explore the perspectives of CSA among older adults living with HIV. Methods: Twenty-four adults living with HIV aged 50 to 67 years (mean age = 58.5 years), with a history of CSA, receiving care from an HIV clinic in South Carolina, participated in the study. In-depth semi-structured interviews were conducted, audio recorded and analyzed using a thematic analytic approach. The iterative analytic process included a three-step approach: discussion of initial thoughts and key concepts, identification and reconciliation of codes, and naming of emergent themes. Results: Four themes emerged: Psychological issues due to CSA, relationship challenges due to CSA, self-blame, and reliving childhood trauma (subtheme: lack of influence of CSA today). Some participants reported feeling the influence of CSA several years after the event while others noted that that there was a lack of influence of CSA at present. Conclusions: Trauma-informed intervention programs are needed for older adults living with HIV who still experience the influence of their CSA experience. Future research should delve into the design and feasibility of implementing these programs.